Hybrid solar power plant with thermochemical energy storage: A multi-objective operational optimisation. (1st February 2020) - Bravo, R.; Ortiz, C.; Chacartegui, R.; Friedrich, D.
Highlights: Validated linear optimisation model for calcium-looping process integrated with CSP. Multi-objective operational optimisation for hybrid solar power plants with TCES. Multi-objective optimisation is key to balance competitiveness and dispatchability. Configurations described as case studies can achieve capacity factors around 70%. Affordable full-dispatchability possible in locations with excellent solar resource. Abstract: Energy storage is key to decarbonising the energy sector by reducing intermittency and increasing the integration of renewable energy. Thermochemical energy storage (TCES) integrated with concentrated solar and photovoltaic power plants, has the potential to provide dispatchable and competitive energy. Here we develop a multi-objective optimisation framework to find the best operational strategy of a hybrid solar power plant with a TCES system. The model uses a typical meteorological year to optimise one-year hourly operation. The results demonstrate that the integration of a calcium-looping process as TCES in a concentrated solar power plant provides dispatchability and, when hybridised with photovoltaic, enhances its competitiveness with current electricity prices. The low mismatch between supply and demand, even when a fixed commitment is required throughout the year, together with a high overall efficiency, indicates that the integration of calcium-looping in hybrid solar power plants is an opportunity to increase the penetration of solar energy in the power sector. Through the optimisation framework presented, a seasonal energy storage analysis can be developed, although a second optimisation stage is required to improve the sizing of the main components of the system in order to further reduce the energy costs.